Returns to Human Capital Under The Communist Wage Grid and During the Transition to a Market Economy - Münich, Daniel; Svejnar, Jan; Terrell, Katherine (The Review of Economics and Statistics, 2005)
We estimate returns to human capital during communism and the transition using data on 2,284 men in the Czech Republic. We show: (a) extremely low and constant rates of return to education under the communist wage grid and dramatic increases in transition, which do not differ by firm ownership, (b) radical changes in returns to several fields of study and “sheepskin effects” in both regimes, (c) identical wage experience profile in both regimes, (d) similar 1996 returns to human capital obtained in communism and in transition, and (e) changes in the interindustry wage structure. A decomposition of the variance of wages finds individuals' unobservable effects from communism to persist into transition, but most of the variance is due to unobservable effects introduced in the transition.